(untitled) - Yang, C. N. (Singapore, 1991)
This is book should interest a wide audience of readers. The main lectures are good authoritative reviews of the field and are written in a non technical language. Physicists with a broad interest in cosmology and particle theory and also historians of science should find this book useful.
Keywords: Physicists,Quantum theory,Nhà vật lý,Thuyết lượng tử; Biography,Tiểu sử; Sweden